In search of beauty in music: A scientific approach to musical esthetics - Seashore, Carl E. (New York Ronald Press Company, 1947)
In Search of Beauty in Music A SCIENTIFIC APPROACH TO MUSICAL ESTHETICS by CARL E. SEASHORE. PREFACE: MORE HAS BEEN ACHIEVED in the laying of foundations for science in music in the present century than in all preceding centuries. The chief reason for this is that the applied science of music has had to await the development of such underlying sciences as acoustics, physiology, electrical engineering, anthro pology, experimental education, and experimental psychology. In all these fields phenomenal progress has been made in the instrumentation and standardizing of techniques of measure ment. Naturally to these should be added the development of a body of science-minded musical artists who welcome such scien tific approaches. The progress has been facilitated and rushed at phenomenal speed by the practical aspects of radio, phono photography, phonography, industrial acoustics, and the increas ing demands for the psychology of music in these fields, as well as in education. During this period of extraordinary expansion in the basic sciences which contribute to the scientific foundations of music, it has been my great fortune to be associated with scientists and musicians who have been interested in cultivating a closer affilia tion between science and music through teaching, lecturing, writing, and the direction of research. This volume is designed as an introduction to the science of music for advanced students of music and psychology, music teachers, educators, professional musicians, and general readers interested in the scientific approach to the understanding and appreciation of beauty in music. It is an attempt to integrate my interpretive and popular articles on research in the psychol ogy of music which have more or less direct bearing on the problem of esthetics. Each chapter has appeared in whole or in part in some leading musical, scientific, or educational journal. Since the book opens a large variety of new fields of thought and investigation, the reader is advised to turn to the table of contents for a preliminary orientation by deliberate examination of the listings of specific topics where he can identify familiar items and new items in which he may be interested. In collecting this material I have aimed to organize these articles into a unified series while retaining as far as possible the original form and setting, whether used in whole or in part or assembled under a single group heading. This has the advan tage of presenting each topic in readable and newsy style, gen erally in direct address to some specific audience or reading constituency. The need of this becomes evident when it is seen that each of the 35 chapters virtually opens a new avenue of approach to the psychology of music and esthetics and presents masses of research findings which are new to the majority of readers. Each article or unit of an article opens up a new vista for discovery and exploration which must be grasped as a more or less new idea, each in its individual field, and yet with due regard for the unity in the theme of the book as a whole...